An in vitro study on the biocompatibility of WE magnesium alloys. Issue 3 (1st May 2015) - Ge, Shuping; Wang, Yi; Tian, Jie; Lei, Daoxi; Yu, Qingsong; Wang, Guixue
Abstract: Magnesium alloys are being actively studied for intravascular stent applications because of their good mechanical strength and biocompatibility. To rule out the high allergenicity of nickel and neurotoxicity of aluminum element, four kinds of WE magnesium alloys (where "W" represents the metallic element Y and "E" represents mixed rare earth (RE) elements; Y: 2.5, 5.0, 6.5, and 7.5 wt %; Nd: 1.0, 2.6, 2.5, and 4.2 wt %; Zr: 0.8 wt %) were chosen for in vitro investigation of their biocompatibility using cell culture. The results showed that, with the increase of rare earth elements in WE magnesium alloys, fibrinogen adsorption decreased and coagulation function was improved. It was also found that WE magnesium alloys promoted the adhesion of endothelial cells. With the increase of adhesion time, adhered cell numbers increased gradually. With 25% extracts, all the WE alloys promoted cell migration, while 100% extracts were not conducive to cell migration. Based on the above results, WE magnesium alloys 5.0WE (5.0Y‐2.6Nd‐0.8Zr) and 6.5WE (6.5Y‐2.5Nd‐0.8Zr) have better biocompatibility as compared with that with 2.5WE (2.5Y‐1.0Nd‐0.8Zr) and 7.5WE (7.5Y‐4.2Nd‐0.8Zr), and could be as the promising candidate materials for medical stent applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 482–487, 2016.